2021
DOI: 10.1017/s0022215121000840
|View full text |Cite
|
Sign up to set email alerts
|

ENT trainees’ experience of redeployment during the coronavirus disease 2019 pandemic: a qualitative study

Abstract: Background. As a response to the acute strain placed on the National Health Service during the first wave of coronavirus disease 2019 in the UK, a number of junior doctors including ENT trainees were redeployed to other clinical specialties. This presented these trainees with novel challenges and opportunities. Methods.A qualitative study was performed to explore these experiences, undertaking semi-structured interviews with ENT trainees between 17th and 30th July. Participants were recruited through purposefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…11 It is imperative to acknowledge that when an individual is redeployed to a new team, they can feel unsupported and undervalued due to uncertainty and team dynamics. 22 Contemporary patient care is delivered in a team environment and can only be improved when the multidisciplinary team works effectively together. 23 A growing body of literature demonstrates the association between the quality of teamwork to the overall safety and excellence of healthcare, resulting in reduced clinical incidents, enhanced patient satisfaction and better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is imperative to acknowledge that when an individual is redeployed to a new team, they can feel unsupported and undervalued due to uncertainty and team dynamics. 22 Contemporary patient care is delivered in a team environment and can only be improved when the multidisciplinary team works effectively together. 23 A growing body of literature demonstrates the association between the quality of teamwork to the overall safety and excellence of healthcare, resulting in reduced clinical incidents, enhanced patient satisfaction and better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that positive redeployment experience is the key determinant of staff satisfaction. When redeployed to a new team, it is common to feel unsupported and undervalued due to uncertainty of team dynamics [11]. Therefore, it is unsurprising that feeling welcomed and supported were the key factors identi ed by the respondents to result in a positive experience.…”
Section: Discussionmentioning
confidence: 99%
“…A thoughtful ‘qualitative’ study from London, UK, is included this month, which examines a small number of ENT trainees and investigates their feelings about redeployment during the Covid-19 pandemic. 8 This study should help in the planning of redeployment should future similar situations arise. Many aspects of the psychological effects are discussed, as well as the trainees’ feelings about their skill sets not being fully utilised.…”
mentioning
confidence: 96%